THE FIRST RECORD OF PERMIAN FLORA IN THE ANSILTA FORMATION (WESTERN PRECORDILLERA OF ARGENTINA) AND ITS REGIONAL CORRELATION (Ameghiniana, 2014)
Key words. Conifer. Glossopteris. Paleoflora. Permian. Argentina.Palabras clave. Conífera. Glossopteris. Paleoflora. Pérmico. Argentina.